The Implementation Of Digital Audio Workstation Learning In Digital Music At Art Drama, Dance, And Musicstudy Program Of Padang State University - Hidayat, Rian; Syafwandi, Syafwandi (LANGGAM: International Journal of Social Science Education, Art and Culture, 2022)
This study aimed to determine, describe and analyze the facilities and infrastructure for Digital Music lectures at the Art, Drama, Dance and Music Study Program of UNP, the use of DAW as the primary medium for learning Digital Music at the Art, Drama, Dance and Music Study Program, Universitas Negeri Padang, and the implementation of digital audio workstations in the Digital Music lectures of the Art, Drama, Dance and Music Study Program, Universitas Negeri Padang. This type of research was descriptive qualitative research. The main instrument in this study was the researcher himself and assisted by supporting instruments such as stationery, camera, memory card /flash disk, and mobile phone. This study's data sources were lecturers and students of the Art, Drama, Dance and Music Study Program, Universitas Negeri Padang. The informants of this research are lecturers in Digital Music lectures at the the Art, Drama, Dance and Music Study Program, Universitas Negeri Padang. Data collection techniques were carried out using library research, observation, and interviews. The steps to analyze the data were data collection, data reduction, data presentation, and concluding. The results showed inadequate facilities and infrastructure for digital music lectures. The facilities and infrastructure only use computers and soundcards in digital music lectures. Meanwhile, the facilities needed in digital music lectures are computers, soundcards, mixers, microphones, and midi controllers. The Sibelius, Nuendo, and fruity loop software were used in this lecture. However, students still expect the provision of software from the lecturer without trying to download the software. The implementation of the classes for this course went well. It was following the RPS used by the lecturer in charge of digital music courses, so the material provided was well conveyed. However, in implementing a Digital Audio Workstation, many students could not operate it properly, whether operating Sibelius, Nuendo, or fruity loop. As music academics, students should at least master notation writing and music editing to have skills in work after graduating from college.